ANALISIS BIOMEKANIKA GERAKAN KARATE TEKNIK TENDANGAN MAWASHI GERI - Nurhadi, Maha Dewi Afifah; Resty, Resty Gustiawati; Wijaya, Habibi Hadi (Jurnal Arena Olahraga Silampari, 2023)
Martial arts since it was first introduced by Gichin Funakoshi with the term "Tote", meaning like "Chinese Hand". Then Gichin Funakoshi changed it to "Karate" which means "empty hand" according to Japanese Kanji so that Japanese people are more receptive. The Mawashi Geri kick is a basic movement or kihon. Biomechanics is a science that uses the laws of physics and engineering theory to study the movements of several parts of the body and the forces that occur in those parts during daily activities. This study uses a systematic literature review (SLR) literature review method with a bibliometrics approach. Data sources were taken in the study using journal articles with a time span of 5 years previously in 2020-2024 sourced from the Google Scholar database and several relevant journal articles. One of the software used for database searches is Publish Or Perish. The publication of articles each year experiences a decrease and increase. In 2021, the publication of articles increased with a total of 3 articles which was consistent from the previous year with a total of 1.92%. And in 2020 the percentage was 4.34% as well as in 2022 and 2023 the percentage difference of 0.5% decreased in article publications. Then in 2024 no article publications were found on the keywords. By expanding the keywords used and the databases accessed, future research will be more effective. Keywords: Biomekanika, Karate, Mawashi-Geri, Tendangan